Determination of Oxidative Stress in Pleopodal Eggs of Propolis-Feeding Crayfish - Yonar, Serpil Mişe (Durmuş Ali ARSLAN, 2023)
Propolis is a sticky, resinous substance that has a unique smell and can vary in color from light brown to black, collected by bees from the leaves, buds, branches and bark of trees to protect themselves from cold and diseases. Propolis, an immunostimulant substance with properties such as antimicrobial, antibacterial, anticarcinogenic, antifungal, antiviral, antitumor, antiparasitic, antiprotozoan, anti-inflammatory, anesthetic, antioxidant and antiseptic, has attracted a lot of attention in recent years. In this study, changes in malondialdehyde (MDA) and glutathione (GSH) levels were investigated in pleopodal eggs taken from crayfish to which propolis was added to the feed at different rates. For this purpose, trial feeds containing 0% (control), 0.5% (D1), 1% (D2) and 2% (D3) propolis were created. At the end of 90 days of feeding, pleopodal egg samples were taken from crayfish. MDA and GSH levels were investigated in the samples taken. It was determined that MDA levels decreased in the pleopodal eggs of the propolis applied groups (p < 0.05). It was observed that GSH levels in pleopodal eggs increased (p < 0.05). It can be said that propolis has a protective effect against oxidative stress in crayfish eggs and can reduce stress during the reproductive period.

Propolis, arıların kendilerini soğuktan ve hastalıklardan korumak için ağaçların yaprak, tomurcuk, dal ve kabuklarından topladığı yapışkan, kendine özgü kokusu olan, açık kahverengiden siyaha kadar rengi değişebilen reçinemsi karakterdeki maddedir. Antimikrobiyal, antibakteriyel, antikanserojen, antifungal, antiviral, antitümör, antiparaziter, antiprotozoan, antiinflamatuar, anestetik, antioksidan, antiseptik gibi özelliklere sahip immünostimulan yapıda bir madde olan propolis son yıllarda oldukça fazla dikkat çekmektedir. Bu çalışmada, farklı oranlarda yeme katılan propolisin uygulandığı kerevitlerden alınan pleopodal yumurtalarda malondialdehit (MDA) ve glutatyon (GSH) düzeylerindeki değişimler araştırıldı. Bu amaçla % 0 (kontrol), % 0.5 (D1), % 1 (D2) ve % 2 (D3) oranlarında propolis içeren deneme yemleri oluşturuldu. 90 günlük besleme sonunda, kerevitlerden pleopodal yumurta örnekleri alındı. Alınan örneklerde MDA ve GSH düzeyleri araştırıldı. Propolis uygulanan grupların pleopodal yumurtalarında MDA düzeylerinin azaldığı belirlendi (p < 0, 05). Pleopodal yumurtalardaki GSH düzeylerinin ise arttığı (p < 0,05) gözlemlendi. Propolisin kerevit yumurtalarında oksidatif strese karşı koruyucu bir etki gösterdiği ve üreme döneminde stresi azaltabileceği söylenebilir.
Propolisle Beslenen Kerevitlerin Pleopodal Yumurtalarında Oksidatif Stresin Belirlenmesi
Keywords: Shellfish Culture; Kabuklu Su Ürünleri Yetiştiriciliği